Managing Tax Dispute Due to IFRS-16 on the Retrofits Implementation in Indonesia - Nasip, Ismiriai; Sudarmaji, Eka (International Journal of Engineering and Technology, 2018)
The IFRS-16 will shortly be implemented worldwide, where the operating lease is effectively removed, and all operational leases are qualified as debt. The operational lease is a major source and is important for off-balance sheet financing in Indonesia. Therefore, the implementation of IFRS-16 will probably hurt Indonesian business. The contract and/or service level agreements on the retrofits for the energy efficiency product can relieve the business owner from cash flow and new debts. This study established a framework for a critical comparative study; compare and assess the possibility of the retrofit financial practices under the current taxes regime, and the possibility upon IFRS-16 implementation to better understand the favorable measures for retrofit practitioners and future customers to handle the disputes. Triangulate the findings of comparative study and questionnaire survey to develop recommendation for the future researchers, practitioners and the government. The result indicates that the benefits of the retrofits financing implementation beat the cost and complexity posed by the enactment of new IFRS standards. Thus, the impact of the IFRS-16 and taxation are being considered as a part of business constraints that should be addressed together and able to manage the disputes over misperception on retrofits aspects with taxes officers. Â Â